Analisis Strategi Peluang Usaha Fashion Wanita pada Toko Aii Colection di Kota Bandar Lampung - Suhartina; Riska Gita Utami; Soewito (Business Perspective Journal, 2021)
Aii Collection is a fashion store in the clothing business that focuses on fulfilling the needs of women, located on Jln. Pangeran Antasari, Number 8B, Bandar Lampung City. This study analyzes the strategies that can be carried out in order to increase women's fashion business opportunities at the Aii Collection store. The purpose of this research is to find out what strategies can be done to increase sustainable business opportunities at the Aii Colection store by using qualitative research methods. Data collection techniques are field research and interviews, which clearly describe how these factors are interrelated in the Aii Collection effort by analyzing using SWOT analysis and IFE EFE matrix tools. From the research results, SWOT matrix analysis and SWOT cartesius diagram shows that the Aii collection effort is in quadrant I, with values ​​(1.92 and 1.55). Where is a situation that will benefit and it is known that the company is still a developing company. The best strategy that can be applied to the Aii Collection business is the aggressive strategy or the Growth Oriented Strategy. Keywords: IFE EFE, strategy, business opportunities, SWOT